2006
DOI: 10.1016/j.neuroscience.2005.08.083
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Linolenic acid and riluzole treatment confer cerebral protection and improve survival after focal brain ischemia

Abstract: We investigated here the effects of alpha-linolenic acid and riluzole, both activators of the 2P-domain K+ channel family TREK/TRAAK, in a model of focal ischemia clinically relevant to stroke, not only assessing neuronal protection, but also long term survival. Moreover, all the drug treatments were initiated post-ischemia. Mice were subjected to transient middle cerebral artery occlusion (1 h) and reperfusion according to the intraluminal filament model. Drugs were injected into the jugular vein according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(102 citation statements)
references
References 38 publications
6
92
0
2
Order By: Relevance
“…In the domain of stroke disorders, there is growing evidence that the omega-3 precursor, ALA, is a potent protector in several models of global and focal ischemia (Xiao et al, 1998;Lauritzen et al, 2000;Blondeau et al, 2001Blondeau et al, , 2002Blondeau et al, , 2007Lang-Lazdunski et al, 2003;Heurteaux et al, 2004Heurteaux et al, , 2006a. In a mouse model of stroke, we found that a single injection of ALA, after the onset of stroke, significantly reduced infarct size and improved the neurological score 24-h post-ischemia.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…In the domain of stroke disorders, there is growing evidence that the omega-3 precursor, ALA, is a potent protector in several models of global and focal ischemia (Xiao et al, 1998;Lauritzen et al, 2000;Blondeau et al, 2001Blondeau et al, , 2002Blondeau et al, , 2007Lang-Lazdunski et al, 2003;Heurteaux et al, 2004Heurteaux et al, , 2006a. In a mouse model of stroke, we found that a single injection of ALA, after the onset of stroke, significantly reduced infarct size and improved the neurological score 24-h post-ischemia.…”
Section: Introductionmentioning
confidence: 64%
“…In a mouse model of stroke, we found that a single injection of ALA, after the onset of stroke, significantly reduced infarct size and improved the neurological score 24-h post-ischemia. Although the single injection of ALA did not improve long-term survival rate, repeated ALA injections over 3 weeks significantly improved survival, suggesting that subchronic ALA treatment triggers other protective pathways (Heurteaux et al, 2006a).…”
Section: Introductionmentioning
confidence: 86%
“…TREK-1 has been previously reported to play an important role in neuroprotection against acid pathological condi tions [4,7,12,26] . In electrophysiological studies, some lipids substantially increase the probability of these K2P channels being open, thus hyperpolarizing the membrane potential and reducing neuronal excitability [12,[27][28][29][30] . This action on the part of lipids would be predicted to counteract the neuronal damage that arises from the increased membrane excitability that often accompanies CNS insults such as ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…␣-linolenic acid has been demonstrated to lower platelet aggregation 25 and to be cross-sectionally related to less carotid artery atherosclerosis, 26 and administration has also been suggested as a promising target for neuroprotection after focal brain ischemia. 27 In summary, the relations of fatty acid patterns to stroke incidence are to some extent still unclear. A weak epidemiological correlation between hypercholesterolemia and increased risk for stroke has been demonstrated.…”
Section: Wiberg Et Al Metabolic Risk Factors For Strokementioning
confidence: 99%